Stress Analysis of Pin Connections in Steel Box Girder with the Unibridge System using Finite Element Model - Ayu Sinta Aprilia; Ali Awaludin; Suprapto Siswosukarto; Ngudiyono Ngudiyono (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study analyzes the Unibridge system, a modular steel box girder employing two pins for longitudinal connections, thereby expediting construction compared to traditional girders. A finite element model was developed to analyze the stress on these pins in a single-box girder with five segments and a reinforced concrete floor slab. Various loads were applied following the Indonesian bridge loading standard, SNI 1725:2016. The model considers operational load analysis and assumes full composite behaviour between the top flanges of the girder and the concrete floor slab. The results indicate that the Von-Mises stress on the pins reaches a maximum of 490.95 MPa under combined service loads, consistently remaining below the specified material yield stress limit of 1200 MPa. Consequently, the Demand Capacity Ratio (DCR) is 0.41. As a result, the Unibridge girder connection pins do not experience plastic deformation under the applied loads.